Production of Recombinant Laccase From Coprinopsis cinerea and Its Effect in Mediator Promoted Lignin Oxidation at Neutral pH - Kontro, Jussi; Lyra, Christina; Koponen, Milla; Kuuskeri, Jaana; Kähkönen, Mika A.; Wallenius, Janne; Wan, Xing; Sipilä, Jussi; Mäkelä, Miia R.; Nousiainen, Paula; Hildén, Kristiina (Frontiers in Bioengineering and Biotechnology, 2021)
Laccases are multi-copper oxidases that use molecular oxygen as the electron acceptor to oxidize phenolic and indirectly also non-phenolic substrates by mechanisms involving radicals. Due to their eco-friendliness and broad substrate specificity, laccases span a wide range of biotechnological applications. We have heterologously expressed a laccase from the coprophilic basidiomycete Coprinopsis cinerea (CcLcc9) in the methylotrophic yeast Pichia pastoris. The recombinant CcLcc9 (rCcLcc9) oxidized 2,6-dimethoxyphenol in the neutral pH range, and showed thermostability up to 70°C. The rCcLcc9 efficiently oxidized veratryl alcohol to veratraldehyde in the presence of low molecular weight mediators syringyl nitrile, methyl syringate and violuric acid, which are syringyl-type plant phenolics that have shown potential as natural co-oxidants for lignocellulosic materials. In addition, rCcLcc9 is able to depolymerize biorefinery hardwood lignin in the presence of methyl syringate and syringyl nitrile as indicated by gel permeation chromatography, and infrared spectral and nucleic magnetic resonance analyses. Furthermore, we showed that several added-value aromatic compounds, such as vanillin, vanillic acid, syringaldehyde, syringic acid and p-hydroxybenzoic acid, were formed during sequential biocatalytic chemical degradation of biorefinery lignin, indicating that rCcLcc9 harbors a great potential for sustainable processes of circular economy and modern biorefineries.